2006
DOI: 10.1590/s0073-47212006000300008
|View full text |Cite
|
Sign up to set email alerts
|

Nova espécie de Pimelodus (Siluriformes, Pimelodidae) dos rios Tapajós e Tocantins, Brasil

Abstract: ABSTRACT. A new species of Pimelodus (Siluriformes, Pimelodidae) from Tapajós and Tocantins rivers, Brazil. Pimelodus tetramerus sp. nov. differs from the other species of Pimelodus Lacepède by its typical coloration, with four dark stripes on the sides of the body, the most dorsal beginning just behind the pre-dorsal plate and finishing at the end of the adipose-fin base; the second, wider than the first one, running just above the lateral line and extending from the lateral border of the supra-occipital proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Among the great catfishes, the Steindachneridion and Pseudoplatystoma genera occupy the top of the alimentary chain; present great load and migrate in at least a phase of the life (Miranda, 1997;Revaldaves et al, 2005). The genus Pimelodus has the greatest diversity in the Pimelodidae family, with 26 species distributed from Panama to Argentina, ranging from small to medium-size (Lundberg & Littmann, 2003;Ribeiro & Lucena, 2006a, 2006b. The genus Sorubim is distributed in hydrographic basins of the Amazon, Orinoco, Paraná and Paraíba Rivers (Froese & Pauly, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among the great catfishes, the Steindachneridion and Pseudoplatystoma genera occupy the top of the alimentary chain; present great load and migrate in at least a phase of the life (Miranda, 1997;Revaldaves et al, 2005). The genus Pimelodus has the greatest diversity in the Pimelodidae family, with 26 species distributed from Panama to Argentina, ranging from small to medium-size (Lundberg & Littmann, 2003;Ribeiro & Lucena, 2006a, 2006b. The genus Sorubim is distributed in hydrographic basins of the Amazon, Orinoco, Paraná and Paraíba Rivers (Froese & Pauly, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, each has centrum 7 exposed ventrally and the superficial ossification is restricted to more anterior vertebrae . It is important to emphasize that this character exhibits different ontogenetic states, including an exposed seventh vertebral centrum (Azpelicueta, 2001;Ribeiro & Lucena, 2006b). Lundberg et al (1991b), and Lundberg & Parisi (2002) also identified one derived state of the trigeminofacial nervecomplex (and respective foramina), which diagnoses a group of Pimelodus species, including P. maculatus (type-species).…”
Section: Discussionmentioning
confidence: 99%
“…Osteological terminology follows Lundberg & Luckenbill (2007). Comparative material is that listed by Ribeiro & Lucena (2006a, 2006b and additional specimens listed below under "Additional Examined Specimens". Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bloch's catfish is one of eight species of Pimelodus Lacépède occurring in the Amazon River drainage system. This is a highly appreciated and the most consumed species in the region, considered by locals to be a tasty and cheap fish (Padovani et al , 1996; Boujard et al , 1997; Ribeiro & Lucena, 2006).…”
Section: Introductionmentioning
confidence: 99%